2014
DOI: 10.26719/2014.20.12.796
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of stigma among hepatitis B and C patients in Rawalpindi and Islamabad, Pakistan

Abstract: Hepatitis B and C are chronic diseases with mental and social impacts which can result in poor quality of life. The aim of this study was to determine the experiences of stigma in a sample of hepatitis B-and C-positive patients in Pakistan. In a cross-sectional study, 140 inpatients and outpatients from 3 tertiary-care hospitals in Islamabad and Rawalpindi answered a semi-structured questionnaire about stigma experienced from relatives, friends, spouse and health-care providers, and about work/financial proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 21 publications
5
21
2
2
Order By: Relevance
“…Our study showed that three-fourths of Chinese CHB patients experienced discrimination because of their hepatitis B infection, and that many suffered severe discrimination [ 7 , 17 19 ]. The experience of discrimination was associated with strongly negative feelings and mental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that three-fourths of Chinese CHB patients experienced discrimination because of their hepatitis B infection, and that many suffered severe discrimination [ 7 , 17 19 ]. The experience of discrimination was associated with strongly negative feelings and mental stress.…”
Section: Discussionmentioning
confidence: 99%
“…The attitudes towards CHD surgical scarring in our study findings were unique. Unlike a study from Canada where the majority of adolescents with CHD were comfortable disclosing their condition without the fear of being stigmatised [39], CHD is a source of stigma in Pakistan [40,41]. Genetic diseases are negatively perceived [41], primarily due to decreased prospects for marriageability and in part due to a fear of genetic transmission to the next generation [40].…”
Section: Discussionmentioning
confidence: 89%
“…There is persistent rise in toll of infected patients. This can be correlated with poor hygienic living conditions, overcrowding and lack of awareness regarding spread of communicable diseases [12,13]. Overall prevalence of HCV is reported to be 6% with range from 3% to 6% [14], but reported to be much higher in interior Sindh as compared to other parts of country [15].…”
Section: Introductionmentioning
confidence: 99%